PHARMACOLOGICAL STRATEGIES FOR THE TREATMENT OF BIPOLAR DISORDER IN PREGNANT WOMEN: A SYSTEMATIC REVIEW - Paweł Grzesikowski; Paulina Klich (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Bipolar affective disorder (BAD) is a chronic mental disorder characterized by recurrent episodes of mania or hypomania and depression, with periods of remission in between. In women of reproductive age, BAD is associated with an increased risk of early pregnancy, perinatal complications, and postpartum relapse. The cornerstone of treatment is pharmacotherapy, including mood stabilizers as well as antipsychotic and antidepressant drugs. Pharmacological treatment during pregnancy reduces the risk of relapse but carries a potential risk of developmental defects and obstetric complications. Optimal therapeutic management requires individualized treatment. Aim of the study: The aim of this work was to review the available literature on the pharmacological treatment of bipolar affective disorder (BAD) in pregnant women and to summarize the current state of knowledge. The safety profile of the drugs used and their effects on the mother and fetus during BAD pharmacotherapy are presented. Methods and materials: A review of the literature available in the PubMed database was conducted using the following keywords: „treatment of bipolar disorder during pregnancy”, „teratogenicity”, „mood stabilizers”, „lithium”, „antidepressants”, „antipsychotic agents”, „congenital malformations”, „bipolar depression”, „valproate”, „lamotrigine”, „carbamazepine”, „postpartum relapse” and „anticonvulsants”. Conclusion: Treatment of bipolar affective disorder in women of reproductive age is a significant clinical challenge. Continuation of pharmacotherapy during pregnancy is crucial for mood stabilization and prevention of postpartum episodes. Drug selection should be based on a risk–benefit assessment. Individualized pharmacotherapy and regular monitoring of mother and fetus are essential for optimal treatment outcomes and safety of both mother and child.